Challenges of Online Teaching during the pandemic COVID-19: Reports from Moldovan Vocational Education and Training Teachers - Stiopca, Oleg; Cobb, Robert; Faulkner, Paula E. (European Scientific Journal, ESJ, 2020)
Teachers worldwide are experiencing challenges with transitioning from face-to-face to online teaching during the pandemic COVID-19. Policymakers, school administrators, students, parents, and teachers have all been impacted. Moldovan educational policies and infrastructures are being re-visited to identify the best strategies for supporting its teachers during this time. The purpose of this case study was to assess Moldovan Vocational Education and Training (VET) teachers’ challenges faced teaching online. Data were analyzed by researchers reviewing interview notes to ascertain the main points gathered from teachers occurred during the focus group interview. The focus group with mostly female teachers revealed their desire to gain online teaching training and frustration over a lack of stable Internet connection during lessons. It was concluded that teachers’ needs should be shared with policymakers and school administrators to ensure technology training and reliable technology devices for at home use be provided while schools are closed. Based on conclusions, the following recommendations would be to assess student’s needs to ensure their needs are aligned with teachers’ needs so the best teaching and learning can occur.